Gestational diabetes mellitus: does treatment modality predict the obstetric and neonatal outcome? - John, Lopamudra B.; P., Reddi Rani; Ghose, Seetesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Gestational diabetes mellitus (GDM) may be controlled with dietary modifications alone or may require insulin treatment. This study aims to find out the impact of these two treatment modalities on the maternal and neonatal outcomes. Methods: This retrospective observational study divided the GDM patients into two groups, A and B, treated with diet and insulin therapy respectively and the maternal and neonatal outcome parameters were compared. Results: 299 (6.7%) GDM patients over a period of two years were divided into group A (n=222) and group B (n=77). Need for induction of labour was significantly higher in group B (p=0.02). More number of history of previous abortions were seen in group A (p=0.1) and higher number of emergency Caesarean sections were observed in group B (p=0.1). Previous history of intrauterine deaths, gestational hypertension and hypothyroidism in the present pregnancy, meconium stained liquor, large for gestational age babies and need for neonatal intensive care were comparable in the two groups. Conclusions: There are no significant differences in the pregnancy outcomes of GDM treated with diet therapy alone or insulin except for a higher number of induced labours in the insulin treated group.